Cognitive and emotional empathy in acute and remitted anorexia nervosa: a systematic review - Gray, Indigo E.; Enticott, Peter G.; Fuller-Tyszkiewicz, Matthew; Kirkovski, Melissa (Frontiers in Psychiatry, 2024)
Impairments in empathy are well established in anorexia nervosa (AN). It is unclear, however, whether these deficits only occur in the acute phases of AN due to neurocognitive impacts of starvation (often referred to as context-dependent, or state-like), or if deficits remain once remission has been achieved (trait-like). This debate is commonly referred to as the 'state vs trait' debate. Objective: This systematic review aims to summarise existing literature regarding empathy in AN, and to investigate whether empathy deficits in AN are state-or trait-based. Method: A total of 1014 articles were identified, and seven articles remained after the screening process. These seven articles, comparing empathy across three groups (acute AN, remission of AN, and non-clinical controls), were evaluated and summarised in accordance with PRISMA guidelines. Articles were required to have included all three groups and report on either cognitive empathy and/or emotional empathy. Results: The majority of studies were of satisfactory quality. The results identified were inconsistent, with few articles lending some support to the 'state' hypothesis and others producing nonsignificant results. Conclusions: There is minimal literature comparing empathy in acute and remission phases of AN. While there were some inconsistencies in included articles, some data indicate that there may be slight improvements to emotional and cognitive empathy following recovery of AN. Further research is needed to better enrich knowledge regarding the role of state vs trait with regard to neurocognitive difficulties experienced by individuals with AN.